PTU-014 Relationship between Ferritin/MCV and GI Pathology in Patients Referred from Primary Care with Iron Deficiency Anaemia. (17th August 2016) - Atallah, E; Kumar, S; Chatharoo, S; Agrawal, A
Abstract : Introduction: Iron deficiency anaemia (IDA) is common with BSG guidance suggesting Gastrointestinal (GI) blood loss from colonic or gastric cancer, and malabsorption in coeliac disease are the most important causes. 1 Serum ferritin, microcytosis and hypochromia are the most sensitive markers for iron deficiency. 2 Our objective was to investigate the correlation between MCV/ferritin and GI pathology in patients with IDA by comparing GI pathology in patients with low ferritin versus normal ferritin; and in patients with microcytosis versus normocytosis. Methods: Retrospective cohort study for consecutive patients who had undergone bi-directional endoscopy and/or GI imaging to investigate unexplained anaemia were included. Data was retrieved including Hb, MCV, folate, B12, co-morbidities and findings at endoscopy, histology and imaging were recorded. Patients with normal haemoglobin as per our laboratory's cut off were excluded. Included patients were stratified according to serum ferritin and MCV into 2 groups (low/normal) for each marker. We used the cut-off concentration as per our local laboratory (10 µg/l for ferritin and 78 FL for MCV). The outcome assessed was any GI pathology found that may explain the IDA. Data was analysed including and excluding the diagnosis of gastritis/oesophagitis as possible GI causes of anaemia. Results: 265 included patients (mean age: 68; range: 16–91 years old; 124 males and 141 females) had undergone GI investigations for IDA. Of these, 84 patients had low ferritin (31.6%) whereas 181 patients had normal ferritin. GI pathology excluding gastritis/oesophagitis occurred in 40 (47.6%) and 68 (37.5%) patients in low and normal ferritin group respectively. P = 0.12. Based on MCV, 96 patients had low MCV (36.2%) whereas 169 patients had normal MCV. GI pathology occurred in 38 patients in low MCV group (39.5%) and in 70 patients with normal MCV (41.4%), P = 0.76. No differences were noted upon including gastritis/oesophagitis. Conclusion: There was no clinical or statistical difference in GI pathology in patients presenting with anaemia with or without evidence of iron deficiency. Although a significant number of patients had a GI workup despite no evidence of iron deficiency, the lesion pickup was similar in both groups. Therefore, our study demonstrates the MCV/ferritin might be sensitive markers for IDA but they don't correlate with GI pathology. References: 1 Gut 2011;60 :1309e–1316. doi:10.1136/gut.2010.228874 2 Prevalence of hypochromia vs microcytosis in iron deficiency. Clin Lab Haematol 2000;22 :79e80. Disclosure of Interest: None Declared